Thermal Management of Power LED System - Akca, Hakan; Yasa, Yusuf; Ayaz, Ramazan; Durusu, Ali; Ajder, Ali; Nakir, Ismail; Tanrioven, Mugdesem (IEEE, 2014)
LEDs are used in many areas today. Street lighting is one of them and high-power LEDs are utilized in this area. Electrical energy is converted into light with an efficiency in 10-25% range. The rest is converted into heat. The generated heat is largely caused from LED chip. Furthermore, Driver circuit would also causes heat rise. Removing of this heat from the system is important in order to LED system efficiency because increasing of temperature causes a reduction of luminous flux. Excellent thermal management plays a significant role in terms of efficiency, reliability and durability. In this study, losses are caused from the LED chip and the heat sink which are part of the LED lighting systems are examined. These elements are thermally analyzed. The impacts of these losses on efficiency will be presented.
Keywords: Energy & Fuels